Hierarchical pore carbon metamaterial for zinc ion supercapacitor and preparation method of hierarchical pore carbon metamaterial
By using ZIF-8 template and DQTT polymer to prepare layered pore carbon metamaterials, the problems of low specific surface area and unstable structure of existing zinc ion supercapacitor electrode materials are solved, and high energy density, excellent cycling stability and super High specific surface area.
Patent Information
- Application Number
- CN202411182843.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-02-21
AI Technical Summary
The electrode materials of existing zinc ion supercapacitors have a low specific surface area and the micropore-mesoporous size ratio is uncontrollable, resulting in low energy storage efficiency and unstable structural structure.
Using ZIF-8 as a soft template, DQTT polymer is uniformly adsorbed on its surface through the force of ZIF-8 capillary, DQTT@ZIF composite material is prepared, and the ratio of micropores and mesopors is controlled through carbonization and activation treatment, and the ratio of micropores and mesopors is prepared. A layered pore carbon metamaterial with an ultra-high specific surface area is produced.
The fine regulation of the microstructure of layered pore carbon metamaterials and the precise design of pore characteristics is achieved, which significantly improves the electrochemical performance of zinc ion supercapacitors, including energy density, power density and cycling stability.
Smart Images

Figure CN119495514A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation, and in particular to a hierarchical porous carbon metamaterial for zinc ion supercapacitors and a preparation method thereof. Background Art
[0002] Supercapacitors are widely used in electric vehicles and hybrid vehicles due to their high power density, long cycle life, and fast charge and discharge capabilities. Compared with traditional supercapacitors, zinc-ion hybrid supercapacitors (ZHSCs) have a wider voltage window and thus higher energy density due to their low redox potential zinc anode. They are also considered to be one of the most promising multivalent hybrid supercapacitors. At present, the commonly used electrode materials for commercial capacitors are carbon materials, which mainly store charge through the electric double layer capacitance characteristics. The performance of electric double layer capacitance (EDLC) is highly dependent on the specific surface area of the carbon material. It is worth noting that a good pore size distribution can provide higher specific capacity and energy density. Studies have shown that micropores smaller than 0.68 nanometers will form a significant diffusion energy barrier for hydrated zinc ions, thereby reducing capacitance and rate performance. In aqueous electrolytes, Zn 2+ The size of the solvated structure formed by the water molecules is between 0.15 and 0.86 nanometers. 2+ Coordinated with 6 water molecules, it forms a large particle size of 0.86 nanometers [Zn(H2O)6] 2+ Therefore, suitable pore size can improve the energy storage efficiency of Zn-ion capacitors.
[0003] Hierarchical porous carbon materials have become the focus of scientific research due to their excellent specific surface area, highly ordered pore structure, and outstanding chemical and thermodynamic stability. In particular, their potential applications in energy storage and catalysis have attracted widespread attention. At present, there are still some shortcomings in the preparation technology of hierarchical porous carbon materials, such as relatively low specific surface area, uncontrollable micropore-mesopore size ratio, low energy storage efficiency, and unstable structure. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention discloses a hierarchical porous carbon metamaterial for zinc ion supercapacitors and a preparation method thereof. The prepared hierarchical porous carbon metamaterial has a controllable surface structure, ultra-high specific surface area and pore volume, rich heteroatom content, and good electrochemical stability. The material has the potential to be used as an electrode material for zinc ion supercapacitors, and is expected to significantly improve its electrochemical performance, including but not limited to improving energy density, power density and cycle stability.
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] On the one hand, the present invention provides a hierarchical porous carbon metamaterial for zinc ion supercapacitors, which is a 2D / 3D Z-shaped heterostructure with ZIF-8 micropores and DQTT polymer mesoporous structures on the surface. After carbonization, activation and acid washing, the pore size of the ZIF-8 micropores ranges from 0.89 to 0.97 nm, the pore size of the DQTT polymer mesopores ranges from 3.5 to 6.5 nm, and the specific surface area is 3073.1 to 5292.1 m 2 / g.
[0007] Another aspect of the present invention provides a method for preparing a hierarchical porous carbon metamaterial for a zinc ion supercapacitor, the steps of which are as follows:
[0008] (1) Preparation of ZIF-8:
[0009] A 1-1.5 mmol / mL 2-methylimidazole anhydrous methanol solution is added dropwise to a 0.1-0.2 mmol / mL zinc nitrate hexahydrate anhydrous methanol solution, stirred and mixed, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene for heating. The obtained product is washed with N,N-dimethylformamide (DMF) and methanol, and the obtained precipitate is ZIF-8. After vacuum drying at 45-55° C., it is set aside. The volume ratio of the 2-methylimidazole anhydrous methanol solution to the zinc nitrate hexahydrate in anhydrous methanol solution is 1:1.5-2.5;
[0010] (2) Preparation of DQ@ZIF composite materials:
[0011] Dissolve 2,6-diaminoanthraquinone (DQ) in N,N-dimethylformamide (DMF), then add ZIF-8, shake and react, filter to obtain a precipitate after the reaction is completed, and then dry at 40-60° C. to obtain a DQ@ZIF composite material; the mass of the 2,6-diaminoanthraquinone, the mass of the ZIF-8, and the volume ratio of N,N-dimethylformamide are 25-100 mg: 0.8-1.2 g: 100 mL;
[0012] (3) Preparation of hierarchical porous carbon metamaterials:
[0013] The obtained DQ@ZIF composite material is dispersed in acetonitrile to obtain an acetonitrile solution of the DQ@ZIF composite material, and added to a 2,4,6-trichloro-1,3,5-triazine (TT) acetonitrile solution with a concentration of 0.8-3.2 mg / mL, stirred, filtered, washed with ethanol and dried to obtain a hierarchical pore precursor, wherein the mass ratio of the DQ@ZIF composite material to the volume ratio of acetonitrile is 0.8-1.2 g:30-40 mL in the acetonitrile solution of the DQ@ZIF composite material; and the volume ratio of the acetonitrile solution of the DQ@ZIF composite material to the 2,4,6-trichloro-1,3,5-triazine acetonitrile solution is 2-3:1;
[0014] The hierarchical porous precursor is heated to 700-850°C at a rate of 4-6°C / min in a tube furnace and carbonized for 1-2 hours. The carbonized hierarchical porous precursor is mixed with potassium hydroxide at a mass ratio of 1:0.5-1.5, and then placed in a tube furnace. Under the protection of inert gas, it is heated to 900-1200°C at a rate of 4-6°C / min for activation and maintained for 1-2 hours. After natural cooling, it is pickled and dried to obtain a hierarchical porous carbon metamaterial.
[0015] Furthermore, in step (1), the heating temperature is 110-130° C., and the reaction time is 1-3 h.
[0016] Furthermore, the temperature of the oscillation reaction in step (2) is 28-35° C., the rotation speed is 100-140 r / min, and the time is 15-20 h.
[0017] Furthermore, the stirring temperature in step (3) is 75 to 85° C. and the stirring time is 2 to 4 hours.
[0018] Furthermore, in step (3), the carbonization temperature is 800-850°C, and the activation temperature is 1000-1100°C.
[0019] Furthermore, in step (3), the mass ratio (activation ratio) of the carbonized hierarchical porous precursor to potassium hydroxide is 1:0.8-1.2.
[0020] Furthermore, the inert gas in step (3) is nitrogen or argon.
[0021] Furthermore, the solvent for pickling in step (3) is HF / HCl.
[0022] The advantages and positive effects achieved by the present invention are:
[0023] 1. The present invention uses ZIF-8 as a soft template, and the DQTT polymer formed by 2,6-diaminoanthraquinone and 2,4,6-trichloro-1,3,5-triazine can be uniformly adsorbed on its surface through the capillary force of ZIF-8 to obtain a DQTT@ZIF composite material. After carbonization, the hierarchical porous carbon metamaterial with different proportions of ZIF-8 micropore-DQTT mesopore structure is obtained by controlling the activation ratio, thereby achieving fine regulation of the microstructure and precise design of the pore characteristics.
[0024] 2. The hierarchical porous carbon metamaterial prepared by the present invention is in situ grown on the outer surface of ZIF-8 by a two-dimensional cyclic organic covalent polymer (DQTT), forming a 2D / 3D Z-shaped heterostructure, which has an ultra-high specific surface area after carbonization and activation.
[0025] 3. When the hierarchical porous carbon metamaterial prepared by the present invention is used in zinc ion supercapacitors, the specific capacity at 0.5A / g can reach 252.9mAh / g, and the specific capacity after 5000 cycles of charge and discharge at a high current density of 5A / g is maintained at 111.3mAh / g, showing excellent long-cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 (ac) scanning electron microscope images, (d) transmission electron microscope images, and (e) high-resolution magnified images of the hierarchical porous carbon metamaterial of Example 1 of the present invention;
[0027] Figure 2 A comparison diagram of nitrogen isothermal adsorption-desorption curves tested on the hierarchical porous carbon metamaterials of Examples 1 to 3 of the present invention;
[0028] Figure 3 A comparison diagram of the pore size distribution curves of the hierarchical porous carbon metamaterials tested in Examples 1 to 3 of the present invention;
[0029] Figure 4 The comparison diagrams of (ac) transmission electron microscopy, (de) transmission electron microscopy at high resolution, and (gi) crystallization obtained by fast Fourier transform for testing the hierarchical porous carbon metamaterials in Examples 1 to 3 of the present invention;
[0030] Figure 5 This is a comparison diagram of the contact angles of electrodes prepared in Examples 1 to 3 of the present invention;
[0031] Figure 6 It is a comparison diagram of the constant current charge and discharge curves of the hierarchical porous carbon metamaterials in Examples 1 to 3 of the present invention;
[0032] Figure 7 (a) charge-discharge cycle characteristic curve and (b) rate performance curve of the zinc ion capacitor assembled with the hierarchical porous carbon metamaterial in Example 2 of the present invention;
[0033] Figure 8 (ab) scanning electron microscope images and (cd) high-resolution magnified images of the comparative example and Example 2 of the present invention. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with the embodiments. The following embodiments are descriptive rather than restrictive, and the protection scope of the present invention cannot be limited by the following embodiments.
[0035] The various experimental operations involved in the specific embodiments are all routine techniques in the art. For parts not specially annotated in this document, ordinary technicians in the art can implement them by referring to various commonly used reference books, scientific and technological literature or related instructions, manuals, etc. before the filing date of this invention.
[0036] Example 1
[0037] A method for preparing a hierarchical porous carbon metamaterial for zinc ion supercapacitors, comprising the following steps:
[0038] (1) Preparation of ZIF-8:
[0039] 150 mL of anhydrous methanol containing 2-methylimidazole (160 mmol) was added dropwise to 300 mL of anhydrous methanol containing zinc nitrate hexahydrate (40 mmol). After stirring for 30 min, the mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated at 120 °C for 2 h. The obtained product was washed three times with N,N-dimethylformamide (DMF) and three times with methanol. The obtained precipitate was ZIF-8, which was vacuum dried at 50 °C for later use.
[0040] (2) Preparation of DQ@ZIF composite materials:
[0041] 50 mg of 2,6-diaminoanthraquinone (DQ) was dissolved in 100 mL of N,N-dimethylformamide (DMF), and then 1 g of ZIF-8 obtained in step (1) was added, and the reaction was oscillated at 30°C at a speed of 120 r / min for 18 h. After the reaction was completed, the precipitate was obtained by filtration and then dried at 50°C to obtain a DQ@ZIF composite material.
[0042] (3) Preparation of hierarchical porous carbon metamaterials:
[0043] Disperse 1 g of the DQ@ZIF composite material obtained in step (2) in 35 mL of acetonitrile to obtain an acetonitrile solution of the DQ@ZIF composite material, add 2,4,6-trichloro-1,3,5-triazine (TT, 12 mg) dissolved in 15 mL of acetonitrile, stir at 80° C. for 3 h, filter, wash with ethanol and dry to obtain a hierarchical porous precursor;
[0044] The hierarchical porous precursor was heated to 800°C at a rate of 5°C / min in a tube furnace and carbonized for 1 hour. The carbonized hierarchical porous precursor was mixed with potassium hydroxide in a mass ratio of 1:0.8 and then placed in a tube furnace. Under the protection of nitrogen gas, it was heated to 1000°C at a rate of 5°C / min and activated for 1 hour. After natural cooling, the carbon powder was washed with HF / HCl and dried to obtain a hierarchical porous carbon metamaterial.
[0045] The (ac) scanning electron microscopy images, (d) transmission electron microscopy images, and (e) high-resolution magnified images of the hierarchical porous carbon metamaterial prepared in Example 1 are shown in FIG. Figure 1 shown.
[0046] Example 2
[0047] A method for preparing a hierarchical porous carbon metamaterial for zinc ion supercapacitors, comprising the following steps:
[0048] (1) Preparation of ZIF-8:
[0049] 150 mL of anhydrous methanol containing 2-methylimidazole (160 mmol) was added dropwise to 300 mL of anhydrous methanol containing zinc nitrate hexahydrate (40 mmol). After stirring for 40 min, the mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated at 125°C for 1.5 h. The obtained product was washed three times with N,N-dimethylformamide (DMF) and three times with methanol. The obtained precipitate was ZIF-8, which was vacuum dried at 50°C and set aside.
[0050] (2) Preparation of DQ@ZIF composites
[0051] 50 mg of 2,6-diaminoanthraquinone (DQ) was dissolved in 100 mL of N,N-dimethylformamide (DMF). Then 1 g of ZIF-8 was added and the mixture was shaken at 33°C and 130 r / min for 16 h. After the reaction was completed, the precipitate was filtered and dried at 60°C to obtain the DQ@ZIF composite material.
[0052] (3) Preparation of hierarchical porous carbon metamaterials:
[0053] Disperse 1 g of the DQ@ZIF composite material obtained in step (2) in 35 ml of acetonitrile to obtain an acetonitrile solution of the DQ@ZIF composite material, add 2,4,6-trichloro-1,3,5-triazine (TT, 12 mg) dissolved in 15 mL of acetonitrile, stir at 80° C. for 4 h, filter, wash with ethanol and dry to obtain a hierarchical pore precursor;
[0054] The hierarchical porous precursor was heated to 810°C at a rate of 6°C / min in a tube furnace and carbonized for 2 hours. The carbonized hierarchical porous precursor was mixed with potassium hydroxide in a mass ratio of 1:1 and placed in a tube furnace. Under the protection of argon gas, it was heated to 1000°C at a rate of 5°C / min and activated for 1 hour. After natural cooling, the carbon powder was washed with HF / HCl and dried to obtain a hierarchical porous carbon metamaterial.
[0055] Example 3
[0056] A method for preparing a hierarchical porous carbon metamaterial for zinc ion supercapacitors, comprising the following steps:
[0057] (1) Preparation of ZIF-8:
[0058] 150 mL of anhydrous methanol containing 2-methylimidazole (160 mmol) was added dropwise into 300 mL of anhydrous methanol containing zinc nitrate hexahydrate (40 mmol). After stirring for 30 min, the mixture was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated at 130 °C for 2 h. The obtained product was washed three times with N,N-dimethylformamide (DMF) and three times with methanol. The obtained precipitate was ZIF-8, which was vacuum dried at 50 °C for later use.
[0059] (2) Preparation of DQ@ZIF composite materials:
[0060] 50 mg of 2,6-diaminoanthraquinone (DQ) was dissolved in 100 mL of N,N-dimethylformamide (DMF). Then, 1 g of ZIF-8 obtained in step (1) was added, and the mixture was shaken at 28°C at a speed of 140 r / min for 20 h. After the reaction was completed, the precipitate was obtained by filtration and then dried at 50°C to obtain a DQ@ZIF composite material.
[0061] (3) Preparation of hierarchical porous carbon metamaterials
[0062] Disperse 1 g of the DQ@ZIF composite material obtained in step (2) in 35 mL of acetonitrile to obtain an acetonitrile solution of the DQ@ZIF composite material, add 2,4,6-trichloro-1,3,5-triazine (TT, 12 mg) dissolved in 15 mL of acetonitrile, stir at 80° C. for 3 h, filter, wash with ethanol and dry to obtain a hierarchical porous precursor;
[0063] The hierarchical porous precursor was heated to 850°C at a rate of 4°C / min in a tube furnace and carbonized for 2 hours. The carbonized hierarchical porous precursor was mixed with potassium hydroxide at a mass ratio of 1:1.2, and then placed in a tube furnace. Under the protection of inert gas, it was heated to 1100°C at a rate of 4°C / min and activated for 1 hour. After natural cooling, the carbon powder was washed with HF / HCl and dried to obtain a hierarchical porous carbon metamaterial.
[0064] Comparative Example 1
[0065] The ZIF-8 prepared in step (1) of Example 1 was heated to 1000° C. at a heating rate of 5° C. / min in a tube furnace under inert gas protection and maintained for 1 h. After natural cooling, the carbon powder was washed with HF / HCl and dried.
[0066] Comparative Example 2 (without activation)
[0067] The only difference from Example 1 is step (3), 1 g of the DQ@ZIF composite material obtained in step (2) is dispersed in 35 mL of acetonitrile to obtain an acetonitrile solution of the DQ@ZIF composite material, 2,4,6-trichloro-1,3,5-triazine (TT, 12 mg) dissolved in 15 mL of acetonitrile is added, stirred at 80° C. for 3 h, filtered, washed with ethanol and dried to obtain a hierarchical porous precursor;
[0068] The hierarchical porous precursor was heated to 800°C at a rate of 5°C / min in a tube furnace and carbonized for 1 hour. After natural cooling, the carbon powder was washed with HF / HCl and dried to obtain a hierarchical porous carbon metamaterial.
[0069] Comparative Example 3 (without carbonization)
[0070] The only difference from Example 1 is step (3), 1 g of the DQ@ZIF composite material obtained in step (2) is dispersed in 35 mL of acetonitrile to obtain an acetonitrile solution of the DQ@ZIF composite material, 2,4,6-trichloro-1,3,5-triazine (TT, 12 mg) dissolved in 15 mL of acetonitrile is added, stirred at 80° C. for 3 h, filtered, washed with ethanol and dried to obtain a hierarchical porous precursor;
[0071] The hierarchical porous precursor was mixed with potassium hydroxide in a mass ratio of 1:0.8, and then placed in a tubular furnace. Under nitrogen gas protection, the mixture was heated to 1000°C at a heating rate of 5°C / min and activated for 1 hour. After natural cooling, the carbon powder was washed with HF / HCl and dried to obtain a hierarchical porous carbon metamaterial.
[0072] Figure 2 and Figure 3 Comparison of nitrogen isothermal adsorption and desorption curves and pore size distribution curves of hierarchical porous carbon metamaterials prepared at different activation ratios of the hierarchical porous precursor and potassium hydroxide after carbonization in Examples 1 to 3. The detection method is: measurement is carried out by a surface area analyzer at a liquid nitrogen temperature of 77K, the degassing temperature is 300℃ / min, and the degassing time is 4h.
[0073] Figure 6 The constant current charge-discharge curves are compared for the hierarchical porous carbon metamaterials of Examples 1 to 3. Detection method: The constant current charge-discharge curves were tested by an electrochemical workstation CHI 660e, with a current density of 0.5 A / g and a voltage window of -0.2 to 0.9 V.
[0074] Figure 7The zinc ion capacitor assembled with hierarchical porous carbon metamaterials in Example 2 was tested for (a) charge and discharge cycle characteristic curves and (b) rate performance curves. Detection method: The hierarchical porous carbon metamaterial in Example 2 was used as the positive electrode active material to prepare the positive electrode, the zinc plate was used as the negative electrode, and assembled into a 2032-type battery shell. The diaphragm was glass fiber, and the electrolyte was zinc trifluoromethanesulfonate. The cycle performance and rate performance were tested using the LAND-CT3001A battery testing system in the voltage range of 0 to 1.5 V. The charge and discharge cycle characteristic curves were tested at a high current density of 5 A / g.
[0075] Table 1 Pore structure parameters of comparative examples 1 to 3 and embodiments 1 to 3
[0076]
[0077] Table 2 Element content parameters of comparative example 1 and examples 1 to 3
[0078]
[0079]
[0080] like Figure 1 It can be seen that the structure of the hierarchical porous carbon metamaterial is stable after carbonization and activation, and DQTT as a mesoporous source grows uniformly on the surface of ZIF-8 along the ZIF-8 crystal plane. Figure 2 and Figure 3 It can be seen that the effects of different activation ratios (mass ratio of hierarchical pore precursor after carbonization to potassium hydroxide) on the pore structure are compared. With the increase of the activation ratio, the specific surface area gradually increases. When the activation ratio is 1:1, the isothermal adsorption-desorption curve is closer to the IV type isothermal adsorption curve, and the hysteresis loop is close to the H2 type. There is a saturated adsorption platform, which reflects that the pore size distribution is relatively uniform. When the activation ratio is 1:1.2, the adsorption platform begins to tilt, and the reaction microporous structure begins to collapse. According to Table 1, the micropore volume of Example 2 is greater than that of Example 3.
[0081] like Figure 4 It can be seen that with the increase of activation ratio, the lattice degree of hierarchical porous carbon metamaterial is higher, that is, the graphitization degree is higher. According to Table 2, with the increase of activation ratio, the heteroatom content gradually decreases. Figure 5 It can be seen that the electrode material prepared in Example 2 has the best permeability. Figure 6 The constant current charge and discharge curves of the hierarchical porous carbon metamaterials of Examples 1 to 3 are compared. It can be seen from the figure that the mass specific capacitance of the hierarchical porous carbon metamaterial of Example 2 is the highest, which is 313.7F / g. Figure 7The zinc ion capacitor assembled in Example 2 was tested for (a) charge and discharge cycle characteristic curve and (b) rate performance curve. After 5000 charge and discharge cycles, the coulombic efficiency was 99.6% and the specific capacity was 111.3 mAh / g.
[0082] Therefore, it can be seen that the DQTT mesoporous structure and the ZIF-8 microporous structure in the hierarchical porous carbon metamaterial prepared by the method of the present invention have a synergistic effect, and the equilibrium relationship between micropores and mesopores can be adjusted by controlling the activation ratio, thereby effectively improving the energy storage efficiency of the electrode material.
[0083] like Figure 8 The surface morphology structures of Comparative Example 1 (a, c) and Example 2 (b, d) are compared. It can be seen from the figure that the surface structure of ZIF-8 after carbonization is smooth and has a clear outline, and a granular structure is uniformly grown on the hierarchical porous carbon metamaterial after in-situ growth of DQTT on ZIF-8.
[0084] Although the embodiments of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments.
Claims
1. A hierarchical porous carbon metamaterial for zinc ion supercapacitors, characterized in that: It is a 2D / 3D Z-shaped heterostructure with ZIF-8 micropores and DQTT polymer mesoporous structures on the surface. After carbonization, activation and acid washing, the pore size of ZIF-8 micropores ranges from 0.89 to 0.97 nm, the pore size of DQTT polymer mesopores ranges from 3.5 to 6.5 nm, and the specific surface area is 3073.1 to 5292.1 m 2 / g.
2. The method for preparing a hierarchical porous carbon metamaterial for zinc ion supercapacitor according to claim 1, characterized in that: Here are the steps: (1) Preparation of ZIF-8: A 1-1.5 mmol / mL 2-methylimidazole anhydrous methanol solution is added dropwise to a 0.1-0.2 mmol / mL zinc nitrate hexahydrate anhydrous methanol solution, stirred and mixed, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene for heating. The obtained product is washed with N,N-dimethylformamide and methanol, respectively, and the obtained precipitate is ZIF-8, which is vacuum dried at 45-55° C. and then used for later use; the volume ratio of the 2-methylimidazole anhydrous methanol solution to the zinc nitrate hexahydrate in anhydrous methanol solution is 1:1.5-2.5; (2) Preparation of DQ@ZIF composite materials: Dissolve 2,6-diaminoanthraquinone in N,N-dimethylformamide, then add ZIF-8, shake and react, filter to obtain a precipitate, and then dry at 40-60° C. to obtain a DQ@ZIF composite material; the mass of the 2,6-diaminoanthraquinone, the mass of the ZIF-8, and the volume ratio of N,N-dimethylformamide are 25-100 mg: 0.8-1.2 g: 100 mL; (3) Preparation of hierarchical porous carbon metamaterials: The obtained DQ@ZIF composite material is dispersed in acetonitrile to obtain an acetonitrile solution of the DQ@ZIF composite material, and the solution is added to an acetonitrile solution of 2,4,6-trichloro-1,3,5-triazine with a concentration of 0.8-3.2 mg / mL, stirred, filtered, washed with ethanol and dried to obtain a hierarchical pore precursor, wherein the mass ratio of the DQ@ZIF composite material to the volume ratio of acetonitrile is 0.8-1.2 g:30-40 mL in the acetonitrile solution of the DQ@ZIF composite material; and the volume ratio of the acetonitrile solution of the DQ@ZIF composite material to the acetonitrile solution of the 2,4,6-trichloro-1,3,5-triazine is 2-3:1; The hierarchical porous precursor is heated to 700-850°C at a rate of 4-6°C / min in a tube furnace and carbonized for 1-2 hours. The carbonized hierarchical porous precursor is mixed with potassium hydroxide at a mass ratio of 1:0.5-1.5, and then placed in a tube furnace under inert gas protection, heated to 900-1200°C at a rate of 4-6°C / min for activation and maintained for 1-2 hours. After natural cooling, it is pickled and dried to obtain a hierarchical porous carbon metamaterial.
3. The preparation method according to claim 2, characterized in that: The heating temperature in step (1) is 110-130° C., and the reaction time is 1-3 hours.
4. The preparation method according to claim 2, characterized in that: The oscillation reaction in step (2) is carried out at a temperature of 28 to 35° C., a rotation speed of 100 to 140 r / min, and a time of 15 to 20 h.
5. The preparation method according to claim 2, characterized in that: The stirring temperature in step (3) is 75-85° C. and the stirring time is 2-4 hours.
6. The preparation method according to claim 2, characterized in that: The carbonization temperature in step (3) is 800-850°C, and the activation temperature is 1000-1100°C.
7. The preparation method according to claim 2, characterized in that: The mass ratio of the carbonized hierarchical pore precursor to potassium hydroxide in step (3) is 1:0.8-1.
2.
8. The preparation method according to claim 2, characterized in that: The inert gas in step (3) is nitrogen or argon.
9. The preparation method according to claim 2, characterized in that: The solvent for pickling in step (3) is HF / HCl.